Revised and Extended Analysis of Five Times Ionized Argon (Ar VI) - Raineri, María Mónica (1992)
The spectrum of five times ionized argon, (Ar VI), has been observed in the 280-2100 Å wavelength range. Eighty-seven lines have been identified as transitions between levels of the $latex 3s^{2}3p$, $latex 3s3p^{2}$, $latex 3s^{2}3d$, $latex 3p^{2}$, $latex 3s3p3d$, $latex 3s^{2}4s$, $latex 3s^{2}4d$ and $latex 3s3p4s$ configurations. For 33 of the lines the classification is new. Forty-one energy level values belonging to these configurations were analyzed and we propose 9 new energy level values for levels corresponding to odd parity configurations. The configurations are interpreted by fitting the theoretical energy expressions to the observed energy levels using least- squares techniques. The parameter values are compared with results from Hartree-Fock calculations.